Effects of rare earth elements (Ce, La) on microstructure and mechanical properties in compacted graphite iron. Issue 3 (1st February 2021) - Zhu, Jianan; Lian, Xintong; Lu, Hengchang; Liu, Qingyi; Jiang, Ailong; Fang, Duo; Dong, Han; Xu, Dexiang
ABSTRACT: Microstructure and mechanical properties of compacted graphite iron (CGI) alloyed with different additions of rare earth (RE) elements are analysed in this paper. Experimental results show that graphite presents mostly vermicular shape when the content of RE is less than 0.041%. The shape of graphite becomes spherical after more RE is added. Tensile strength is improved significantly with the increase of RE content at room temperature and 400°C. Growth rate of main crack decreases obviously after RE alloying during thermal fatigue tests at 600°C. RE elements tend to segregate towards the interface between graphite and matrix, which leads to the change of graphite morphology. Auger electron spectroscopy (AES) results also show that Ce atoms will concentrate towards fracture surface, thus improving the oxidation resistance of the fracture surface at high temperature and crack propagation is inhibited.